(untitled) (Indian Journal of Animal Production and Management, 2025)
The present study was conducted to investigate the effect of supplementation of prebiotics mannan-oligosaccharide (MOS) on antioxidant and thyroid status in SVVU T17 crossbred pigs. Twenty-four SVVU T17 crossbred male grower pigs above 2 months of age were randomly divided into four groups with six piglets in each group i.e., P0, P1, P2 and P3 groups. The experiment was conducted for 45 days and at the end of experiment blood samples were collected for estimation of antioxidants and thyroid levels. There was a significant increase (P